2013
DOI: 10.3109/00016489.2013.816443
|View full text |Cite
|
Sign up to set email alerts
|

Width of the normal facial canal measured by high-resolution cone-beam computed tomography

Abstract: The widths of the facial canal at each point were similar bilaterally (r = 0.54-0.85, p < 0.01), but showed regional differences and site-specific variations. The narrowest of the five sites was the level of the meatal foramen (p < 0.05), as reported previously. The second narrowest site was the level of the stapes (p < 0.01) followed in order by the level of the cochleariform process, the pyramidal eminence, and the point of emergence of the chorda tympanis (p < 0.01).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The mean angle was 22.6 ± 10° and the distance of the electrode to the bony canal of the facial nerve was about 1.8 mm with a thickness of the bony coverage of about 0.8 mm. The diameter of the facial nerve canal was determined at 1.8 mm and is in principal accordance with other studies 31 . Interestingly, a significant difference in the diameter of facial nerve canal could be detected between groups.…”
Section: Discussionsupporting
confidence: 79%
“…The mean angle was 22.6 ± 10° and the distance of the electrode to the bony canal of the facial nerve was about 1.8 mm with a thickness of the bony coverage of about 0.8 mm. The diameter of the facial nerve canal was determined at 1.8 mm and is in principal accordance with other studies 31 . Interestingly, a significant difference in the diameter of facial nerve canal could be detected between groups.…”
Section: Discussionsupporting
confidence: 79%
“…13 In other parts of the horizontal and vertical segments, ossification has delayed, which causes the dehiscence of the bony wall. 11 In the present study, we investigated the relationship between mastoid pneumatization and CP, and the neighboring structures. Because the facial nerve has been found to pass behind the CP and the tensor tympani, it has been recently concluded that the CP is a useful landmark to locate the facial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…After that, it gradually becomes narrower to the level of the stapes and enlarges to the stylomastoid foramen. 11 Ge and Spector 12 reported that ossification on the facial canal labyrinthine segment occurs before the 15th week of pregnancy. Similarly, ossification is performed in the CP, from the 20th week to the 22nd week of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to imaging, intraoperative measuring of stapedius reflex threshold values indicate the correct placement of the electrodes [8]. Cone Beam Computed Tomography (CBCT) offers a low-radiation and cost-effective alternative to conventional CT, while also being superior in visualizing highdensity structures, such as the temporal bone [9]. CBCT provides a reduction of the effective dose of up to 40% of a 64-slice CT [10] and comparable radiation dose to a 128slice CT, but with higher image quality compared to both due to the higher spatial resolution [11,13].…”
Section: Introductionmentioning
confidence: 99%